Key Factors and their Dimensions in Patient Safety Culture in Elderly Care: A Scoping Review - Asri Handayani Solihin,; Christantie Effendy,; Probosuseno, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Safety in elderly patients is a critical health issue, with various studies highlighting safety concerns within the geriatric health care system. Yet, there is no clear understanding of most important things that impact culture of safety among patients residing in nursing homes, clinics and community. Aim:The objective of this research were to determine and examine patients’ safety culture factors in elderly care system and their main elements. Material & Method: A scoping review was conducted using PRISMA-ScR guidelines. A comprehensive search of articles was performed across multiple databases (Pub-Med, Science Direct, Cochrane, CINAHL, and Embase) in August 2021. The inclusion criteria focused on studies related to patient safety culture in geriatric care settings (primary care facilities, nursing homes, and community). Thirty-nine articles were selected for data extraction, which was then mapped onto a Total Safety Culture domain developed for this study. Result: Three key factors—person, environment, and behavior—and twenty dimensions were identified as components of patient safety culture in geriatric care. Conclusion: Future investigations into safety culture in geriatric care should examine environmental factors through surveys to better understand and enhance multidimensional safety culture.